Frequent False‐positive results of lupus anticoagulant tests in plasmas of patients receiving the new oral anticoagulants and enoxaparin. (6th September 2013) - Martinuzzo, M. E.; Barrera, L. H.; D 'Adamo, M. A.; Otaso, J. C.; Gimenez, M. I.; Oyhamburu, J.
Summary Introduction Oral direct thrombin and Xa inhibitors are worldwide distributed for prevention and treatment of thrombosis. It is important to recognize their effects on lupus anticoagulant (LA) testing. The aim of the study is to describe the rate of false‐positive results of LA tests on plasmas of patients with previous negative LA tests results that receive dabigatran etexilate (DAB) 110 mg/twice a day, rivaroxaban (RIV) 10 mg/day or 15 mg/twice a day, or enoxaparin 40 mg/day. Methods Blood was taken between 1.5 and 4 h post administration. Tests evaluated are as follows: prothrombin time, APTT, dilute Russell viper venom time (DRVVT) screen, APTT, and DRVVT mixing studies, index of circulating anticoagulant (ICA) with normal plasma, screen/confirm normalized ratio (NR) for DRVVT and silica clotting time (SCT). Results Plasmas from patients taking DAB (n = 22) presented 100% prolonged APTT and DRVVT with ICA above the cutoff point and 81.8% positive screen/confirm NR, 100% prolonged SCT screen, but 4.5% positive confirmatory NR. All patients receiving RIV at 15 mg/twice a day (n = 4) presented positive DRVVT screen, mixing, and confirmatory tests, 75% and 100% prolonged APTT and SCT screen, with negative screen/confirm NR. Those taking RIV 10 mg/day (n = 22) showed 81.8% prolonged DRVVT screen, 82.3% and 76.5% of them with positive mixing and confirmatory studies. Patients receiving enoxaparin also presented high prevalence of APTT and DRVVT false‐positive results. Conclusion Dabigatran etexilate, RIV, and enoxaparin affect tests for LA not only in screening and mixing, but also in confirmatory studies. We considered that LA testing should not to be performed when patients are taken these drugs, particularly if blood is collected at peak, in order to avoid false‐positive results.